2-Hydroxy-4-Isopropoxy-5-Bromoacetophenone Oxime as an Analytical Reagent for Cu(II) - Desai, J.A.; Desai, K.K. (Asian Journal of Chemistry, 2016)
2-Hydroxy-4-isopropoxy-5-bromoacetophenone oxime (HIBAO) was developed as a new analytical reagent for the gravimetric estimation of Cu(II). In pH range 3.5-8.0 the reagent gives a brown coloured precipitate with Cu(II). Spectrophotometric methods revealed that the stoichiometry of the complex is 1 : 2 (metal : ligand). Beer's law is obeyed up to 76.42 ppm of Cu(II). Molar absorptivity and Sandell’s sensitivity at 400 nm were found to be 6.32 × 102 L mol–1 cm–1 and 0.108 μg/cm2 respectively. The stability constant of Cu(II)-HIBAO complex is found to be 4.25 × 109. Gibb’s free energy change for complex formation reaction was found to be –13.18 kcal/mol. The reagent can be used for the analysis of brass.